Avaliação do potencial efeito antidepressivo do 2-BFI, ligante imidazolínico I2, em camundongos - Tonello, Raquel (2012)
Depression is a complex, chronic and disabling psychiatric disease that carries a high social cost. Among the various classes of antidepressants are the monoamine oxidase A (MAO-A) inhibitors that reduce monoamine metabolism. An important site of MAO-A regulation is the imidazoline-2 binding site (I2). In fact, it was recently shown that 2-imidazoline derivatives, such as 2-(2-benzofuranyl)-2-imidazoline (2- BFI), showed good potency and selectivity in inhibiting in vitro the activity of MAO-A, but the antidepressant potential of this compound and its mechanism of action have not been well defined. Therefore, in this study we investigated the antidepressant-like effect of 2-BFI in mice. For this purpose, we evaluated the effects of 2-BFI in two predictive tests of antidepressant-like activity in animals, the tail suspension test (TST) and forced swimming test (FST). The TSC was utilized after the use of specific antagonists of different receptors involved in depression. 2-BFI (100 and 300 μmol/kg, s.c.) significantly reduced the immobility time on the tail suspension test (TST) without changing locomotion in the open field test. The reduced the immobility time of 2-BFI (100 μmol/kg, s.c.) was confirmed with the forced swimming test (FST). The antidepressant-like effect of 2-BFI (100 μmol/kg, s.c.) in the TST was prevented by pretreatment with idazoxan (0.4 μmol/kg, i.p., a I2 site antagonist), methysergide (4 μmol/kg, i.p., a non-selective serotonergic receptor antagonist) and haloperidol (0.1 μmol/kg, i.p., a non-selective dopaminergic receptor antagonist). The anxiolytic effect of 2-BFI was also evaluated, using the elevated plus-maze test. 2-BFI (300 μmol/kg, s.c.) was able to significantly increase the % of number of entries and the % of time spent in the open arms, indicating that it possesses an anxiolytic effect at high doses. In conclusion, these results suggest that the antidepressant-like effect of 2- BFI might involve serotonergic, dopaminergic and imidazoline systems, and then the imidazoline site could represent a new pharmacological target for the treatment of depression.